Au-delà des «vagues» #moiaussi : cinq ans de mobilisation féministe en musique au Québec (2017-2022) - Blais-Tremblay, Vanessa; Champagne, Lysandre (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2020)
Cet article dresse le portrait de cinq organisations qui militent pour l’équité en musique au Québec depuis 2017 : MTL Women in Music, Femmes* en Musique, Lotus collective MTL Coop, shesaid.so MTL et le réseau DIG! Différences et inégalités de genre dans la musique au Québec. En s’inscrivant dans la longue lignée des travaux critiques en historiographie féministe, l’article rend compte de la pluralité des mobilisations féministes au-delà des « vagues » #moiaussi qui ont ponctué l’actualité musicale québécoise au cours des cinq dernières années. Dans la seconde partie, les autrices détaillent les travaux du réseau D!G. Elles présentent des retombées initiales prometteuses à la fois pour le milieu universitaire et pour les milieux de pratique en ce qui concerne l’épistémologie et les méthodologies de la « musicologie partenariale collaborative féministe ».
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; DIG; LGBTQIA2+; amérique du nord; amériques; approches et analyses; arts; canada; discipline; femmes* artistes; genre; histoire et politique; identités LGBTQIA2+; inégalités; militance; musique; périodes historiques; québec; recherche partenariale; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail

Guerrilla Girls: the art of behaving badly - Guerrilla Girls (Group of artists) (Chronicle Books, 2020)
Guerrilla Girls: The Art of Behaving Badly is the first book to catalog the entire career of the Guerrilla Girls from 1985 to present. The Guerrilla girls are a collective of political feminist artists who expose discrimination and corruption in art, film, politics, and pop culture all around the world. This book explores all their provocative street campaigns, unforgettable media appearances, and large-scale exhibitions. Captions by the Guerrilla Girls themselves contextualize the visuals. Explores their well-researched, intersectional takedown of the patriarchy In 1985, a group of masked feminist avengers'known as the Guerrilla Girls'papered downtown Manhattan with posters calling out the Museum of Modern Art for its lack of representation of female artists. They quickly became a global phenomenon, and the fearless activists have produced hundreds of posters, stickers, and billboards ever since. More than a monograph, this book is a call to arms. This career-spanning volume is published to coincide with their 35th anniversary. Perfect for artists, art lovers, feminists, fans of the Guerrilla Girls, students, and activists You'll love this book if you love books like Wall and Piece by Banksy, Why We March: Signs of Protest and Hope by Artisan, and Graffiti Women: Street Art from Five Continents by Nicholas Ganz.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artivisme; arts; arts visuels et médiatiques; com5170; corps; cours; discipline; histoire de l'art; justice sociale; militance; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; représentation des femme*; régions géographiques; sexisme; sofia; systèmes d'oppressions; thématiques; travail; états-unis

L’intervention féministe sous l’influence de l’intersectionnalité : enjeux organisationnels et communicationnels au sein des organismes féministes au Québec - Marchand, Isabelle; Corbeil, Christine; Boulebsol, Carole (Communiquer. Revue de communication sociale et publique, 2020)
Au Québec, l’intervention féministe se déploie significativement au milieu des années 1970 et se présente comme une alternative, à la fois thérapeutique et politique, aux thérapies traditionnelles dans le champ de la santé mentale et de la lutte contre les violences sexistes, pour soutenir les femmes et défendre leurs droits. Elle repose, entre autres, sur la conscientisation et la reprise de pouvoir, à la fois individuelle et collective, dans une société marquée par la discrimination sexiste. Plus récemment, la popularité de l’intersectionnalité, comme cadre d’analyse théorique, politique et pratique, amène les intervenantes féministes francophones à adopter un regard critique sur leurs approches et leurs postures, en considérant notamment l’imbrication du sexisme avec d’autres formes d’oppression comme le racisme. À partir de plusieurs travaux menés au cours des dernières années auprès de praticiennes, les autrices proposent de réfléchir au développement récent de l’intervention féministe sous l’influence de l’intersectionnalité. Cet article suggère quelques pistes d’analyse sur les enjeux organisationnels et relationnels avec lesquels les groupes et les intervenantes doivent composer dans un contexte social et d’intervention qui se complexifie.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; femmes* racisées; histoire et politique; intersectionnalité; intervention féministe; maisons d'hébergement; militance; organisations féministes; périodes historiques; québec; recherche en milieux de pratique; ressource en ligne; régions géographiques; thématiques; travail

Social movements and the politics of care: Empathy, solidarity and eviction blockades - Santos, Felipe G. (Social Movement Studies, 2020)
This paper develops a perspective of mobilization based on the ethics of care to explore the complexities of political solidarity in social movements. On the one hand, it is interested in the reasons why commonly aggrieved individuals do not always collaborate to confront their oppression. On the other, it explores why sometimes people initiate mobilization for causes that do not benefit them directly. From a care perspective, aggrieved individuals may not mobilize to confront their troubles because some of their caring needs (emotional, identity, and participatory) are not covered. At the same time, empathy motivates people not affected by a grievance to initiate mobilization in support of the oppressed collective. Internal solidarity among those aggrieved may be created during the process of mobilization through care work. The analytical relevance of this model is demonstrated explaining the mobilization of the ‘Platform of Those Affected by Mortgages’, the biggest housing organization in Spain. A care-based approach to mobilization contributes to our analysis of contentious collective action by helping to better understand the complexities of political solidarity and the mechanisms through which organizations foster solidarity among their members.
Keywords: 2000 à aujourd'hui; 2010-2019; care; droit au logement; espagne; europe; militance; mouvements sociaux; périodes historiques; ressource en ligne; régions géographiques; solidarité; thématiques; étude qualitative

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis